Impression of foliar-applied folic acid on coriander (Coriandrum sativum L.) to regulate aerial growth, biochemical activity, and essential oil profiling under drought stress - Khan, Muhammad Tajammal; Ahmed, Shakil; Sardar, Rehana; Shareef, Muhammad; Abbasi, Asim; Mohiuddin, Muhammad; Ercisli, Sezai; Fiaz, Sajid; Marc, Romina Alina; Attia, Kotb; Khan, Naeem; Golokhvast, Kiril S. (Frontiers in Plant Science, 2022)
Drought is one of the major environmental limitations in the crop production sector that has a great impact on food security worldwide. Coriander (Coriandrum sativum L.) is a herbaceous angiosperm of culinary significance and highly susceptible to rootzone dryness. Elucidating the drought induced physio-chemical changes and foliar applied Folic acid (FA; Vitmin B9) mediated stress tolerance mechanism of Coriander has been found a research hotspot under the progressing water scarcity challenges for agriculture. The significance of Folic acid in ameliorating biochemical activities for improved vegetative growth and performance of Coriander under the mild stress (MS75), severe stress (SS50), and unstressed (US100) conditions was examined in this study during two consecutive seasons. Results revealed that the plants treated with 50 mM FA showed highest plant fresh biomass (PFB), leaf fresh biomass (LFB) and shoot fresh biomass (SFB) from bolting stage to seed filling stage under mild drought stress. In addition, total soluble sugars (TSS), total flavonoids content (TFC) and chlorophyll content (Chlb) showed significant results by the foliar application of FA while total phenolic content (TPC) showed non-significant results under MS75 and SS50. It was found that 50 mM of FA upregulated the activity of catalases (CAT), superoxide dismutase (SOD) and ascorbate peroxidase (APX) enzymes in MS75 and SS50 plants compared to untreated FA plants. Thus, FA treatment improved the overall biological yield (BY) and economic yield (EY) regardless of water deficit conditions. FA accompanied plants showed decline in drought susceptibility index (DSI) while improved the drought tolerance efficiency (DTE) indicating this variety to become stress tolerant. The optimum harvest index (HI), essential oil (EO) percentage and oil yield (OY) was found in MS75 followed by SS50 in FA supplemented plants. GC-MS analysis revealed higher abundance of linalool as major chemical constituents of EO followed by α-terpeniol, terpinene and p-Cymene in FA treated SS50 plants. FA can be chosen as shotgun tactic to improve drought tolerance in Coriander by delimiting the drastic changes due to drought stress.